DIFFERENTIATION OF COUNTRY REGIONS ON THE MARKET OF INDIVIDUAL DEPOSITS IN COMMERCIAL BANKS - Svetlana G. Babich (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the dynamics of population deposits in commercial banks in the Russian Federation and demonstrates their growth in all regions of the country. The analysis of regional structure of individual deposits shows their concentration in credit organizations of the Central Federal District. The author grouped entities of the Russian Federation by the value of private deposits, which shows considerable regional differences in the level of depositing private funds in credit organizations. A serious dependence of private deposits in commercial banks on the income of population in regions was demonstrated.